DEFORMATION OF KELUD VOLCANO POST NOVEMBER 2007 LAVA DOME FORMATION - Haerani, Nia
Eruption of Kelud Volcano within 2007 started with increasing in seismic activity on November 2007 and ended with Lava Dome Formation inside Crater Lake on 3 November 2007. This phenomena was the changes of eruption behavior, previous last eruption on February 1990 was explosive one. Research on deformation of Kelud Volcano after November 2007 Lava Dome formation carried out to determine characteristic and mechanism of deformation that has been occurred. Prediction of pressure source location and its geometry was analyzed using two different methods, which are: Mogi Model and Closed Pipe Model. Mogi Model is used based on its common application on volcano area, while Closed Pipe Model based on recent condition of Kelud volcano that plugged by lava dome. Pressure source location determined by both models then validated with seismic, EDM, tilt and geology data. Result from GPS observation method during three period, which are: April, August, and October 2008 showed that vector displacement on each measured point affected dominantly by structural geology forces. Mostly crustal stability after last phase of November 2007 eruption. There also minor displacement as result of magma migration around the points that close to the Lava Dome. Magma migration occurred in a very shallow depth and associated with aseismic zone. Deformation that occurred as result of magma migration toward the surface calculated to determine magma supply and magma injected. The result then compare to illustrate mechanism of deformation during April – October 2008. Comparison of magma supply and magma injected within these periods showed that inflation is still occurred, but it does not supported by surface manifestation. This inflation could be false because of data discontinuity, it is actually a part of deflation trend.